Bioelectrical activity of leg muscles while balancing on slippery surface in academic winter football - Gaevaya, Y. A.; Lu, J.; Feiyan, X.; Ilyin, A. A. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to study the bioelectrical activity of the leg muscles of academic winter footballers while balancing on a slippery surface.